2004
DOI: 10.1109/tns.2004.835097
|View full text |Cite
|
Sign up to set email alerts
|

Proton energy dependence of the light output in gallium nitride light-emitting diodes

Abstract: Gallium nitride (GaN)-based blue-emitting diodes (CREE Model C430-DH85) were irradiated at room temperature with protons in the energy range 2 to 115 MeV at fluences varying from 1 10 11 to 1 10 15 cm 2 . Light output degradation curves were obtained for each energy and the damage constant ( ) associated with these curves was determined according to the theory of Rose and Barnes. For proton energies less than 10 MeV, varies inversely with the proton energy ( ). At higher energies, is consistently above the 1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…[158][159][160][161][162][163][164][165][166][167][168][169][170][171] Recently, the application of GaN-based LEDs has been extended to satellite communication systems for weather forecasting or broadband data transmission due to their high radiation hardness. The materials used in GaN-based LEDs have small lattice constants (a = 3.189 Å, c = 5.186 Å for wurtzite GaN structure) due to their strong bond energies and therefore show superior resistance to damage under radiation environments due to the higher displacement energies compared with other semiconductor systems such as the GaAs used in red LEDs (a = 5.653 Å).…”
Section: Radiation Damage In Ingan/gan Light Emitting Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…[158][159][160][161][162][163][164][165][166][167][168][169][170][171] Recently, the application of GaN-based LEDs has been extended to satellite communication systems for weather forecasting or broadband data transmission due to their high radiation hardness. The materials used in GaN-based LEDs have small lattice constants (a = 3.189 Å, c = 5.186 Å for wurtzite GaN structure) due to their strong bond energies and therefore show superior resistance to damage under radiation environments due to the higher displacement energies compared with other semiconductor systems such as the GaAs used in red LEDs (a = 5.653 Å).…”
Section: Radiation Damage In Ingan/gan Light Emitting Diodesmentioning
confidence: 99%
“…They also observed that the optical properties degraded faster than the electrical properties due to an increase in non-radiative transitions through radiation-induced defect states. Khanna et al 168 reported on the proton energy dependence of light output degradation of AlGaN/InGaN/AlGaN blue LEDs over the energy range of 2-115 MeV.…”
Section: Radiation Damage In Ingan/gan Light Emitting Diodesmentioning
confidence: 99%
“…The physical mechanism which causes a degradation of the light output in irradiated LEDs is an increase of radiation-induced lattice defects [1]. Thereby non-radiative recombination centers are created which compete with radiative centers for excess carriers.…”
Section: Led Device Mo Deling Analysismentioning
confidence: 99%
“…Photonic systems based on optical fibers, such as optical fiber sensors and data transfer systems, are ideally suited for applications where high bandwidth, immunity from electromagnetic interference, low power consumption, and low weight is recommended [1]. In order to operate such systems in a hostile radiation environment one has to know how the single components behave when they are exposed to ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Modulators and optical fibers have previously been irradiated with neutrons within thermal effects [1]. The modulators were unaffected in terms of their reflectance.…”
Section: Introductionmentioning
confidence: 99%